Pengembangan Lembar Kerja Peserta Didik Berbasis Pendekatan Saintifik pada Pembelajaran IPS Siswa Kelas IV - Viandari, Faulia; Krisnawati, Yuni; Yuneti, Armi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop valid, practical, and effective student worksheets using a scientific approach for fourth-grade social studies students at SDIQ Ar-Risalah Lubuklinggau. The research method used was research and development using the 4D development model. The results of this study, based on the validity test conducted by three validators: language experts, material experts, and media experts, yielded an average percentage of 92%, categorized as very valid. Meanwhile, the results of the practicality test for educators were 92%, and for students, 91%, both categorized as very practical. Based on the effectiveness analysis using n-gain calculations, the average interval was 0.73, categorized as very effective. The conclusion is that student worksheets based on a scientific approach can be used in fourth-grade social studies instruction at SDIQ Ar-Risalah Lubuklinggau. Keywords: Student Worksheets, Scientific Approach, Development, Social Studies Learning